2022
DOI: 10.1186/s13613-022-01094-6
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of acute kidney injury in critically ill patients with COVID-19: a prospective cohort

Abstract: Background Acute kidney injury (AKI) is common in critically ill patients with coronavirus disease-19 (COVID-19). We aimed to explore the changes in AKI epidemiology between the first and the second COVID wave in the United Kingdom (UK). Methods This was an observational study of critically ill adult patients with COVID-19 in an expanded tertiary care intensive care unit (ICU) in London, UK. Baseline characteristics, organ support, COVID-19 treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We observed a higher rate of patients with non-renal recovery ≥7 days in our cohort. We cannot exclude that these discrepancies were partly due to differences in the definition of renal recovery: we used normalization of SCr while Lumlertgul et al used SCr < 1.5 times baseline value, a more sensitive definition [ 48 ]. Additionally, our study shows that patients who made a rapid renal recovery had a better prognosis since AKD was associated with increased mortality at 90 days and mortality was strongly associated with initial AKI stage.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a higher rate of patients with non-renal recovery ≥7 days in our cohort. We cannot exclude that these discrepancies were partly due to differences in the definition of renal recovery: we used normalization of SCr while Lumlertgul et al used SCr < 1.5 times baseline value, a more sensitive definition [ 48 ]. Additionally, our study shows that patients who made a rapid renal recovery had a better prognosis since AKD was associated with increased mortality at 90 days and mortality was strongly associated with initial AKI stage.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Ontario, Canada, showed that second-wave patients who developed COVID-19-associated AKI and required KRT, compared with first-wave ones, were older, had more comorbidities and initiated KRT later after the beginning of COVID-19 symptomatology [20]. A single-center study in England found a lower risk of AKI and need for KRT in the second wave, although these patients were older and had higher frailty scores [21].…”
Section: Plos Onementioning
confidence: 99%